Experimental Investigation and Theoretical Background of the Optimal Control of the Concrete Mixture Forming - Pshinko, Pavlo; Dekhta, Tatyana; Hromova, Olena; Steinbrech, Oksana (Communications - Scientific Letters of the University of Zilina, 2023)
Concrete belongs to the most used building materials, applied in almost all types of constructions (civil, industrial, road, hydraulic, subway constructions, etc.). Currently, the most common is the vibration method of molding concrete and reinforced concrete products.
Keywords: the intensity of vibrations; the optimal control of forming; the inertial current of energy